2016
DOI: 10.1124/jpet.116.234104
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Induces Cardiomyocyte Terminal Differentiation via Epigenetic Repression of Cyclin D2 Gene

Abstract: Dexamethasone treatment of newborn rats inhibited cardiomyocyte proliferation and stimulated premature terminal differentiation of cardiomyocytes in the developing heart. Yet mechanisms remain undetermined. The present study tested the hypothesis that the direct effect of glucocorticoid receptor-mediated epigenetic repression of cyclin D2 gene in the cardiomyocyte plays a key role in the dexamethasone-mediated effects in the developing heart. Cardiomyocytes were isolated from 2-day-old rats. Cells were stained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
(73 reference statements)
3
18
0
1
Order By: Relevance
“…The intrinsic and extrinsic molecular drivers of this process have been under intensive studies 4,[36][37][38][39][40] . Our observation that both glucocorticoids and vitamin D inhibit proliferation of primary neonatal mouse CMs in vitro is consistent with previous reports in culture 21,22,28,29,41 . GR activation inhibits neonatal rat CM proliferation and increases CM binucleation 21,22 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The intrinsic and extrinsic molecular drivers of this process have been under intensive studies 4,[36][37][38][39][40] . Our observation that both glucocorticoids and vitamin D inhibit proliferation of primary neonatal mouse CMs in vitro is consistent with previous reports in culture 21,22,28,29,41 . GR activation inhibits neonatal rat CM proliferation and increases CM binucleation 21,22 .…”
Section: Discussionsupporting
confidence: 93%
“…Our observation that both glucocorticoids and vitamin D inhibit proliferation of primary neonatal mouse CMs in vitro is consistent with previous reports in culture 21,22,28,29,41 . GR activation inhibits neonatal rat CM proliferation and increases CM binucleation 21,22 . Vitamin D treatment reduces expression of c-myc and proliferating cell nuclear antigen, and blocks cell proliferation in rat CM culture 41 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, another recent study has reported that inhibition of neonatal rat cardiomyocyte proliferation following treatment with dexamethasone is due to promoter hypermethylation and transcriptional repression of cell cycle genes, including Ccnd2 (Gay et al, 2016). Gay et al also demonstrated that 5aza-dC reactivated cell proliferation in dexamethasone-treated cardiomyocytes through restoration of Ccnd2 expression, providing further support for a direct role for DNA methylation in regulating transcription of cell cycle genes (Gay et al, 2016).…”
Section: Summary and Future Directionmentioning
confidence: 85%
“…Gay et al also demonstrated that 5aza-dC reactivated cell proliferation in dexamethasone-treated cardiomyocytes through restoration of Ccnd2 expression, providing further support for a direct role for DNA methylation in regulating transcription of cell cycle genes (Gay et al, 2016). Therefore, identification of the direct targets of DNA methylation at specific cell cycle genes is critical to understand the mechanism of postnatal cardiomyocyte cell cycle arrest.…”
Section: Summary and Future Directionmentioning
confidence: 99%